Geobiology - Geobiology (Wiley, 2026)
Geobiology is a multidisciplinary journal at the interface of geoscience, environmental science, and biology, providing a natural home for geobiological research. Our journal explores the relationship between life and the Earth's physical and chemical environment. We are especially look for cross-disciplinary papers with both geological and biological elements, emphasizing the co-evolutionary interactions between life and its physical environment.
FI 0.73
Q2
Keywords: Earth; Space & Environmental Sciences; Paleontology; Paleobiology & Geobiology; Paleontología; Paleobiología; Geobiología; Acuerdos transformativos; Transformative agreements; Ciencias ambientales; Coevolución; Aspectos físicos; Aspectos Químicos